2009
DOI: 10.1111/j.1439-0396.2009.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intramuscular amino acid levels in submaximally exercised horses - a pilot study

Abstract: The time-dependent changes in intramuscular amino acid (AA) levels caused by exercise and by feeding a protein/AA supplement were analysed in nine horses. Horses were submitted to a total of four standardized exercise tests (SETs). Amino acid concentrations were determined prior to, immediately after, 4 and 18 h after exercise. The experiment was subdivided into two consecutive periods of 3 weeks. In each period two SETs were performed. In the second period, horses were given a protein/AA supplement within 1 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
4
6
0
Order By: Relevance
“…Part of the increase seen after intense exercise is due to plasma volume changes and total protein content has been shown to be around 20% higher after this type of exercise on both the RP and HP diets (Connysson et al 2006). Most of the increase in plasma amino acid levels is, however, due to exercise and the alterations seen on both diets agree with earlier observations on horses performing intense exercise (Miller-Graber et al 1990;Essén-Gustavsson et al 1991;Pösö et al 1991;Hackl et al 2009;van den Hoven et al 2009). Interestingly, the increase in BCAA concentration was maintained high until at least 15 min post exercise on diet HP, whereas it had started to decrease within 15 min on diet RP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Part of the increase seen after intense exercise is due to plasma volume changes and total protein content has been shown to be around 20% higher after this type of exercise on both the RP and HP diets (Connysson et al 2006). Most of the increase in plasma amino acid levels is, however, due to exercise and the alterations seen on both diets agree with earlier observations on horses performing intense exercise (Miller-Graber et al 1990;Essén-Gustavsson et al 1991;Pösö et al 1991;Hackl et al 2009;van den Hoven et al 2009). Interestingly, the increase in BCAA concentration was maintained high until at least 15 min post exercise on diet HP, whereas it had started to decrease within 15 min on diet RP.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the increase in BCAA concentration was maintained high until at least 15 min post exercise on diet HP, whereas it had started to decrease within 15 min on diet RP. It has recently been shown that plasma and muscle leucine and isoleucine concentrations are higher post exercise when horses during 6 weeks are given a protein amino acid mixture daily within 1 h after exercise (van den Hoven et al . 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, either of the two pathways and/or both pathways may have been stimulated by the increase in chicken protein levels. In fact, the present study is in accordance with a recent study in which the plasma taurine level was increased by protein supplementation (Van den Hoven et al . 2010).…”
Section: Discussionsupporting
confidence: 94%
“…Recently, van den Hoven et al. (2010) showed that feeding a protein/AA supplement shortly after strenuous exercise significantly increased the 4 h post‐exercise intramuscular concentration of many AA that are supposed to be involved in protein synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Using convenience data and remains of samples gathered during the conduct of a previous study (van den Hoven et al., 2010), this explorative study aimed to gain further insight into the response patterns that are associated with inhibition of exercise‐induced proteolysis by an orally administered protein/AA mixture. In analogy with studies in man, the mRNA expression of ubiquitin in muscle biopsies was chosen as specific marker of muscle proteolysis.…”
Section: Introductionmentioning
confidence: 99%